Given that
\frac{2i-1}{-i-1}2i−1−i−1
=\frac{1-2i}{1+i}=1−2i1+i
=\frac{(1-2i)(1-i)}{(1+i)(1-i)}=(1−2i)(1−i)(1+i)(1−i)
=\frac{1-3i+2i^2}{1-i^2}=1−3i+2i21−i2
=\frac{1-3i+2(-1)}{1+1}=1−3i+2(−1)1+1
=\frac{-1-3i}{2}=−1−3i2
=-1/2-3/2i=−12−32i
Amplitude =\sqrt{(-1/2)^2+(-3/2)^2}=\sqrt{5/2}=√(−12)2+(−32)2=√52
Argument, \theta=-(\pi-\tan^{-1}|\frac{-3/2}{-1/2}|)θ=−(π−tan−1∣∣
∣∣−32−12∣∣
∣∣)
\theta=-108.435^\circθ=−108.435∘
\therefore \frac{2i-1}{-i-1}
=\sqrt{5/2}(\cos(-108.435^\circ)+i\sin(-108.435^\circ))
=\sqrt{5/2}(\cos108.435^\circ-\sin 108.435^\circ)